The Development of E-commerce Practice Teaching Software Based on Online Payment and Settlement - Zhu, Yongyong (International Journal of Online and Biomedical Engineering (iJOE), 2014)
Development of the enterprise e-commerce gives birth to the development of e-commerce professional. The e-commerce teaching, which is with the practical teaching as the core needs to rely on the e-commerce practical teaching software. The development of e-commerce practical teaching software is based on online payments and settlements, in the light of software designâ??s principles of sharing, scalability and reliability, with the processes WEB system process design thinking, adopts SQL2005 database and B/S architecture, based on JAVA, EJB , J2EE, XML open technical interfaces, from the five functional modules of systems management, information management, B2C transactions, B2B transactions as well as certificates and payment to simulate the payment clearing system, the commercial banking system and the front-end payment instrument system. The students can understand the systems, structures and processes of online payment and settlement systems, building intuitive e-commerce operational mode to enhance the practical operational ability and comprehensive quality through the intuitive feelings of e-commerce online payment and settlement systems.